Analisis Efektivitas dan Efisiensi Penerapan Aplikasi Sistem Keuangan Desa (SISKEUDES) Dalam Pengelolaan Keuangan Desa (Studi Kasus pada Desa Tanete Harapan Kecamatan Cina Kabupaten Bone) - Hildayanti; Rini Idayanti; Fitriani (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study aims to determine and analyze the effectiveness and efficiency of the implementation of the Village Financial System Application (SISKEUDES) in financial management in Tanete Harapan Village, Cina District, Bone Regency. The method used is qualitative with a case study approach. Data collection techniques are carried out through in-depth interviews, observations, and documentation. The results of the study indicate that the implementation of the SISKEUDES application has increased the productivity of village officials, facilitated the preparation of financial reports, and saved time and costs compared to manual systems. However, there are still obstacles in the form of limited user understanding which has an impact on the less than optimal management of finances as a whole. Thus, the implementation of SISKEUDES in Tanete Harapan Village is quite effective and efficient in supporting transparency, accountability, and performance of village officials. Even so, an increase in the capacity of human resources and supporting infrastructure is needed so that the use of this application can be maximized in realizing good village financial management